2002
DOI: 10.1038/sj.onc.1206012
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of G1/S cyclins in estrogen-independent proliferation of estrogen receptor-positive breast cancer cells

Abstract: Estrogen receptor-mediated transcription is enhanced by overexpression of G1/S cyclins D1, E or A in the presence as well in the absence of estradiol. Excess of G1/S cyclins also prevents the inhibition of transactivation of estrogen receptor (ER) by the pure antiestrogen ICI 182780. Cyclin D1 mediates this transactivation independent of complex formation to its CDK4/6 partner. This raises the possibility that overexpression of G1/S cyclins renders growth of ER-positive breast cancer hormone-independent and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 50 publications
3
27
1
Order By: Relevance
“…Our studies suggest that cyclin D1 gene upregulation or protein overexpression (data not shown) fail to predict Tam response. This is consistent with several studies that have shown that cyclin D1 levels do not stringently correlate with Tam resistance (51,52). Although our studies are modeling immunohistochemical loss of RB, disruption of RB transcriptional repression can occur through additional mechanisms that could also contribute to Tam resistance.…”
Section: Figuresupporting
confidence: 78%
“…Our studies suggest that cyclin D1 gene upregulation or protein overexpression (data not shown) fail to predict Tam response. This is consistent with several studies that have shown that cyclin D1 levels do not stringently correlate with Tam resistance (51,52). Although our studies are modeling immunohistochemical loss of RB, disruption of RB transcriptional repression can occur through additional mechanisms that could also contribute to Tam resistance.…”
Section: Figuresupporting
confidence: 78%
“…Likewise, cyclin E/cdk2 and cyclin A/cdk2 complexes are responsible for the G 1 /S transition and onset of DNA replication, respectively (Hwang and Clurman, 2005;Mailand and Diffley, 2005). Aberrant expression of cyclins is linked to breast cancer development and progression (Bindels et al, 2002;Akli et al, 2004;Caldon et al, 2006). While cyclin D1 overexpression is generally associated with an ERapositive phenotype and favorable clinical outcome, deregulation of cyclin E and A is linked to induction of centrosome amplification, aneuploidy, loss of ERa and poor outcome (Bindels et al, 2002;Span et al, 2003;Joe et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of cyclins is linked to breast cancer development and progression (Bindels et al, 2002;Akli et al, 2004;Caldon et al, 2006). While cyclin D1 overexpression is generally associated with an ERapositive phenotype and favorable clinical outcome, deregulation of cyclin E and A is linked to induction of centrosome amplification, aneuploidy, loss of ERa and poor outcome (Bindels et al, 2002;Span et al, 2003;Joe et al, 2005). One mechanism for preservation of genomic stability is through p53-mediated control of centrosome homeostasis (Fukasawa, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To establish this predictive value of cyclin-E, only prospective studies with randomization to endocrine treatment could yield irrefutable results. The involvement of cyclin-E with breast cancer prognosis has been attributed to its association with cell cycle regulation and cellular proliferation (Ku¨hling et al, 2003), chromosomal instability (Spruck et al, 1999), or (anti) estrogen-independent growth (Bindels et al, 2002;Dhillon and Mudryj, 2002). Our results strongly indicate that the latter mechanism is of physiological importance in breast cancer.…”
Section: Discussionmentioning
confidence: 99%